The Model of Empowering The Women Victims of Merapi Eruption through Independent Business Literacy Education - - Sujarwo; - Widyaningsih; - Tristanti (LPPM UNY, 2015)
This study was aimed at: (1) generating a guide model of the empowerment of women victims of Merapi eruption through independent businesses literacy education in permanent housing, Glagaharjo, Cangkringan Sleman, (2) improving the women's knowledge, skills and awareness of environmental management for sustainable and productive . The research method used was modi ied Borg and Gall research and development (R D) model . This early stage research generated: (1) issues and potential environmental research, (2) instructional guides in print form and CD learning. The guide has been validated and the result was excellent, so it is feasible. The next stage of the research will be conducting trainings on waste management, fertilizer manufacture, business management and mentoring